If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(x+7)=5(x+7)=
We move all terms to the left:
5(x+7)-(5(x+7))=0
We multiply parentheses
5x-(5(x+7))+35=0
We calculate terms in parentheses: -(5(x+7)), so:We get rid of parentheses
5(x+7)
We multiply parentheses
5x+35
Back to the equation:
-(5x+35)
5x-5x-35+35=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| x^2+5x−36=0 | | 143/220=x/100 | | (z-2)+0.6(5z-1)=2+0=1 | | 139+2x+9x+6x=360 | | 1+5z=10+4z | | 3=2x+23÷5 | | (1/(x^2))-(7/x)+12=0 | | 4x2+3x−7=0 | | 3+5n=1+8n+2* | | 917=b−-168 | | x-3÷x+14=1÷5 | | X/100x75=25 | | 4,066=38(p+35) | | -11g=-693 | | 12c=576 | | 18b=432 | | x=4/7=-2 | | 31y=155 | | 8v-16=2v+44 | | 3-11z=-118 | | .8t=76 | | -/12z=27/20 | | 2*10/b+2b=14 | | (1/x-6)=(2/x+7) | | 254=85-y | | -24=4u+8u+48 | | (4)(60)+x(2)=500 | | (5x-3)^2=169 | | x/9+6=0 | | 285-y=239 | | 17=v/5+2 | | -7q^2-28=0 |